ЎЗБЕКИСТОН ЖАНУБИЙ ҲУДУДЛАРИДА ТАРҚАЛГАН КСИЛОФАГ ҲАШАРОТЛАРГА ҚАРШИ КУРАШ ЧОРА – ТАДБИРЛАРИНИ ТАКОМИЛЛАШТИРИШ - Омонова, Н.Р; Рахматуллаев , А.Ю; Нарзуллаева, Д.Г (Innovative Development in Educational Activities, 2023)
the historical complekx of the madrasah hamed after Dor-us-siyodat in Shahrisabz, Kashkadarya region, which was damaged by the erocn (Anobium punctatatum) tusks and Turkestan (Anacanthotermes turkestanicus) and (Anacanthotermes ahngerianus) Kasbi bask ternits, whose buldings and structures were damadinsg and the villages of Nekuz of Kasan district and Kamashi of Kasbi district.